2012
DOI: 10.5194/bgd-9-4627-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Jena Diversity-Dynamic Global Vegetation Model (JeDi-DGVM): a diverse approach to representing terrestrial biogeography and biogeochemistry based on plant functional trade-offs

Abstract: Dynamic Global Vegetation Models (DGVMs) typically abstract the immense diversity of vegetation forms and functioning into a relatively small set of predefined semi-empirical Plant Functional Types (PFTs). There is growing evidence, however, from the field ecology community as well as from modelling studies that current PFT schemes may not adequately represent the observed variations in plant functional traits and their effect on ecosystem functioning. In this paper, we introduce the Jena Diversity DGVM… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(104 citation statements)
references
References 173 publications
1
103
0
Order By: Relevance
“…Follows and Dutkiewicz (2011) apply this approach to marine ecosystems, while Kleidon and Mooney (2000) use it to predict biodiversity patterns of terrestrial vegetation. The applicability of this method to modelling biogeochemical fluxes of terrestrial vegetation has been successfully demonstrated by the JeDi-DGVM (Pavlick et al, 2012). …”
Section: Model Parametersmentioning
confidence: 99%
“…Follows and Dutkiewicz (2011) apply this approach to marine ecosystems, while Kleidon and Mooney (2000) use it to predict biodiversity patterns of terrestrial vegetation. The applicability of this method to modelling biogeochemical fluxes of terrestrial vegetation has been successfully demonstrated by the JeDi-DGVM (Pavlick et al, 2012). …”
Section: Model Parametersmentioning
confidence: 99%
“…It is possible that a whole suite of traits and inevitable tradeoffs among these traits can lead to alternative plant designs reaching equal vital rates. This circumstance, in fact, challenges simple bivariate statistical analyses and calls for multivariate approaches, where multidimensional quantiles can be fit to one (or several) climatic niche parameters and for more process-based models accounting for this multidimensional optimization process (39,40). Nevertheless, our bivariate regression equations have the advantage that they are intuitive, are straight forward to implement in models, and can easily be used to generate maps visualizing climatic filtering on trait variation (e.g., Fig.…”
Section: Continental Patterns Of Trait Variation and Potential Functimentioning
confidence: 99%
“…Therefore, species distribution would be a response to N and drought in the ecosystem. This approach has been used to improve two dynamic vegetation models (aDGVM, [128]; JeDi-DGVM, [129]). The Jedi-DGVM outperformed other leading dynamic vegetation models for Leaf Area Index (LAI), NPP, CO 2 seasonality, C fluxes, and, in some regions, C stocks [129].…”
Section: Trait-based Modelingmentioning
confidence: 99%
“…This approach has been used to improve two dynamic vegetation models (aDGVM, [128]; JeDi-DGVM, [129]). The Jedi-DGVM outperformed other leading dynamic vegetation models for Leaf Area Index (LAI), NPP, CO 2 seasonality, C fluxes, and, in some regions, C stocks [129]. Incorporating plant traits in the CSIRO Atmospheric Biosphere Land Exchange (CABLE) model improved the biogeographical distribution of major forests that have multiple dominant PFTs [130].…”
Section: Trait-based Modelingmentioning
confidence: 99%